Seasonal nutritional characteristics of livestock forage in south Turkana, Kenya - Coppock, D. Layne; Swift, D.M.; Ellis, J.E.; Waweru, S.K. (1987)
A study undertaken to characterise and contrast some important chemical attributes of herbaceous and nonherbaceous forages selected by Ngisonyoka livestock throughout one annual cycle in Kenya.